Perioperative Complications in Neonatal Surgery: Biliary Atresia and Choledochal Malformations - Wilde, Jim C. H.; Calinescu, Ana M.; Wildhaber, Barbara E. (European Journal of Pediatric Surgery, 2018)
Biliary atresia (BA) and congenital choledochal malformations (CCM) are rare. Both pathologies must (BA) or may (CCM) be operated during the neonatal period or early infancy. We briefly describe the classical operative techniques for both pathologies, followed by the most common and severe perioperative complications encountered during and up to 30 days after surgery in children operated for BA and CCM early in life. For patients with BA, intestinal complications represent the most common and hazardous perioperative surgical complications. Cholangitis is the most frequently encountered medical complication post hepato-porto-enterostomy. For CCM, it seems that neonates encounter little perioperative complications; however, reports are scarce; bile leak and/or cholangitis are the most reported. Overall, for patients with CCM, the literature is ambivalent whether more perioperative complications occur in the younger or in the older patient, and whether these occur more frequently in those symptomatic or asymptomatic at operation. It is difficult to give clear advice for when children with asymptomatic CCM should be operated, and benefits and risks must be carefully counterbalanced. Perioperative mortality for both BA and CCM is low and is reported to be around 1 to 2%.
Keywords: biliary atresia; congenital choledochal malformations; complications; surgery